INOVASI EVALUASI HASIL BELAJAR PENDIDIKAN AGAMA ISLAM (MODEL-MODEL PENILAIAN BERBASIS AFEKTIF) - Fajri Ismail (Faculty of Tarbiyah and Teaching Sciences, Universitas Islam Negeri Raden Fatah Palembang, 2013)
Evaluation is an activity that includes a very systematic measurement and assessment in which there are aspects to the consideration and decision of a program based on standards or criteria have been established before the program runs.Learning is defined as a change in behavior based on the change that comes from yourself, the presence of the stimulus and its interaction with the environment. Results of the study appear as a change in behavior on students, which can be observed and measured in terms of changes in knowledge attitudes and skills.Domains include cognitive learning outcomes that students knowledge, namely affective and psychomotor assessment that students attitudes and skills assessment capabilities (skills) students.Innovation PAI evaluation of learning outcomes more emphasis on Affective learning outcomes assessment model. Model -based assessment PAI Affective learning outcomes assessment emphasizes the feelings, emotions, or the level of acceptance and rejection. Affective domain region is associated with attitudes, talents, interests, values, appreciation (appreciation) and feelings of social adjustment.There are several models of affective -based assessment in the learning process among PAI; assessment with interest scale, attitude scale assessment, assessment by observation (observation), the assessment questionnaires, with anecdotal records assessment and assessment by sociometry.